TECHNOLOGIES OF PEDAGOGICAL INTERACTION: METHODS OF IMPLEMENTATION (Pedagogy of Higher and Secondary Education, 2008)
In article on base of the analysis of innovative processes, occurring in formation, is determined essence and place technology in hierarchies notion: paradigm, model, methods, technology. As one of the first step on way to new technology is considered realignment mechanism pedagogical interaction.